Optimasi Kinerja Mesin Diesel dengan Campuran Biodiesel dan Aluminium Oksida sebagai Nanoadditif - Muh. Abdillah; Wicaksono, Ariawan Bayu; Ishak; Nurhidayanti (Universitas Nusa Putra, 2025)
Biodiesel is an environmentally friendly renewable fuel, but it has lower energy efficiency and can increase nitrogen oxide emissions. This study examines the effect of adding aluminum oxide nanoparticles (Al₂O₃) on the performance of diesel engines fueled with biodiesel. Five fuel combinations were tested: B30 and B30 with Al₂O₃ at concentrations of 30, 50, 70, and 90 ppm. The results show that the addition of Al₂O₃ increases the engine's torque and brake power, with the highest increases of 4.14% and 6.22% respectively in the B30+Al₂O₃ 70 ppm mixture under high load conditions. This effect is associated with better atomization, optimal air-fuel mixing, and the catalytic properties of the nanoparticles. However, at a concentration of 90 ppm, there is a slight decrease in performance due to nanoparticle aggregation. The optimal concentration of 70 ppm shows potential for improving biodiesel efficiency. Further studies are needed to evaluate the long-term stability and its impact on engine lifespan.